Factors Influencing Investment Decisions in Capital Market: a Study of Individual Investors in Nigeria - Obamuyi, Tomola Marshal (Organizations and Markets in Emerging Economies, 2013)
The study seeks to determine the main factors influencing investment decisions of investors and how these factors are related to the investors’ socio-economic characteristics in the Nigerian Capital Market. The study covers individual investors using convenient sampling method to obtain information from 297 respondents through a modified questionnaire developed by Al-Tamimi (2005). Independent t- test, Analysis of variance (ANOVA) and post hoc tests were employed. The results indicate that the five most influencing factors on investment decisions of investors in Nigeria are past performance of the company’s stock, expected stock split/capital increases/bonus, dividend policy, expected corporate earnings and get-rich-quick. Also, the five least influencing factors include religions, rumors, loyalty to the company’s products/services, opinions of members of the family and expected losses in other investments. The study finds that the socio-economic characteristics of investors (age, gender, marital status and educational qualifications) statistically and significantly influenced the investment decisions of investors in Nigeria. With regard to the past performance of the company’s stock as an assessing factor, groups of investors statistically differed in factor assessment, as segments of a group considered the factor as the most important/unimportant. Since the identified most influencing factors are usually classified as wealth maximising factors, the study recommends that the investment climate and the market environment be made friendly and conducive to attract investors by creatively developing programmes and policies that impact on investors’ decisions in order to maximise the value of the firms and enhance the wealth of the investors. The market players should re-organise the market and implement accommodating policies which will eliminate fraud and resolve the leadership crisis in the market.